A política de educação profissional do governo Dilma : o direito à educação no contexto da expansão da rede federal de educação profissional e do Pronatec - Maciel, Samanta Lopes (2016)
The historical and hegemonic form of basic and professional education in Brazil has been constituted through a type of school supply and qualification by actions and programs that have not yet succeeded in overcoming the structural duality between intellectual work and manual work. They emphasize the educational duality that destines precarious basic public education for early insertion in the labor work for "everybody" and they also destine good quality education related to higher education for "few people". On the other hand, the proposed expansion of the EPCT Federal Network, started in 2005 during president Lula government (2003 to 2010), in a context of economic growth and revenue growth. It expanded the role of the State offering basic and professional Education through the Federal Institutes foundation. President Lula government consolidated the bases for structuring the offer of Technical and Professional Education Integrated to High School. President Dilma government (2011 to 2016), while continuing the Institutes expansion, in a context of a deepening capital crisis and also fiscal crisis, it launches Pronatec, prioritizing the supply of short courses and channeling large huge resources to the System S, the government limits the process of structuring the right to basic and professional education. Considering the materiality resulting from this process, this work aimed to analyze the right to professional education in Brazil at the Federal Network also in Ifes campus São Mateus from 2011 to 2014. From the conception of work as an ontological and historical form, we based on historical-dialectical materialism as a theoretical-methodological reference. As a research technique, we worked with documentary analysis and interviews with the subjects involved in the Integrated Technical Courses and from Ifes Campus São Mateus. The results of this research demonstrated that although Pronatec has as one of its actions to strengthen and to democratize the Federal Network and professional education in the country, the core of its incidence focused on System S offer. They also indicated that the Federal Network Expansion, by establishing the Integrated Higher Education offer as a priority, places itself as a structuring action of the State, strengthening professional education as a right. In parallel, the priority established with Pronatec, with the offer of FIC courses, contributed much less to the consolidation of the right to education and work, as it reproduced the process of precarious training for the occupation of low-skilled jobs, and low remuneration, reinforcing the reproduction of the false duality between training for manual labor and intellectual work